PENGARUH KESELAMATAN KESEHATAN KERJA, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI CV NAENAMU FURNITURE DI SOLO - Reni Puspita Cahyaningsih; Asih Handayani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the significance of the influence of occupational health and safety (OHS), motivation, and work discipline on employee performance. This research uses a quantitative research type. The research utilizes primary data. The sampling technique used is saturated sampling with a total of 51 respondents. The data collection method employs a questionnaire distributed through the chairman or leader. The instrument test in this research uses validity and reliability tests. The classic assumption test uses multicollinearity test, heteroscedasticity test, and normality test. The analysis technique uses multiple linear regression analysis with t test, F test, and R2.The results of the validity and reliability tests show that all statements regarding occupational health and safety, motivation, and work discipline are declared valid because the p-value < 0.05 and reliable because Cronbach's alpha > 0.60. The results of the classical assumption tests indicate that all variables have passed the multicollinearity test, heteroscedasticity test, and are normally distributed. The results of the regression analysis obtained Y = 4.879 + 0.307 X1 - 0.109 X2 + 1.184 X3. The t-test results show that the occupational health and safety (K3) variable significantly influences the performance of production employees at CV Naenamu Furniture, motivation does not significantly influence the performance of production employees at CV Naenamu Furniture, and work discipline significantly influences the performance of production employees at CV Naenamu Furniture. The F-test results indicate that the regression model used in this study is appropriate. The R2 test results show that the contribution of independent variables to the dependent variable is 52.9%. The remaining (100% - 52.9%) = 47.1% is influenced by variables outside the research model.